2009
DOI: 10.1080/09273940802491884
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Neuronal Expression of the Immune Regulator, Programmed Death 1 (PD-1), Identified During Experimental Autoimmune Uveitis

Abstract: PD-1 and its ligands were expressed in sites of active inflammation, in accordance with many other models of inflammatory disease. Surprisingly, PD-1, not previously described outside the immune system, was constitutively expressed in retinal neurons, raising the possibility that PD-1 signaling may be important for neuronal function in the absence of an inflammatory insult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…34 In addition to altering the ratios of CD4 + T-cell subpopulations and correcting the inflammatory milieu, PD-L1 also showed the effects of changing BBB integrity and inhibiting cell loss after ICH. Because PD-1 has been reported to be constitutively expressed on neurons 7 and astrocytes, 9 it is conceivable that the interaction of PD-L1 with PD-1 expressed by neurons and astrocytes would lead to intensifying neuron and astrocyte loss in the PD-L1 group but ameliorate that status in the anti-PD-L1 mAb group, which is in contrast to our results. In the presence of PD-L1, there would be more neuron and astrocyte death because of PD-L1/PD-1 interactions but less cell damage from toxic factors like IL-1 and IL-6 released by proinflammatory Th1 and Th17 cells.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…34 In addition to altering the ratios of CD4 + T-cell subpopulations and correcting the inflammatory milieu, PD-L1 also showed the effects of changing BBB integrity and inhibiting cell loss after ICH. Because PD-1 has been reported to be constitutively expressed on neurons 7 and astrocytes, 9 it is conceivable that the interaction of PD-L1 with PD-1 expressed by neurons and astrocytes would lead to intensifying neuron and astrocyte loss in the PD-L1 group but ameliorate that status in the anti-PD-L1 mAb group, which is in contrast to our results. In the presence of PD-L1, there would be more neuron and astrocyte death because of PD-L1/PD-1 interactions but less cell damage from toxic factors like IL-1 and IL-6 released by proinflammatory Th1 and Th17 cells.…”
Section: Discussioncontrasting
confidence: 99%
“…6 Both PD-1 and B7-1 are reported to be expressed on neurons 7,8 and astrocytes. 9,10 B7-1 associates with PD-L1 with an affinity of about one third the affinity of PD-L1 for PD-1.…”
mentioning
confidence: 99%
“…Identification of PD-1 and it’s ligands in the retina and the establishment of their role in developmental RGC apoptosis has introduced a novel molecular mechanism for RGC death: that RGC apoptosis may be turned on by a negative signal delivered by receptor-ligand interaction through the PD-1 system (Chen et al, 2009a; Chen et al, 2009b; Sham et al, 2012). In this study we further demonstrate that PD-1 is dramatically upregulated in some RGCs after optic nerve injury, raising the possibility that PD-1 signaling pathway might be functionally important in pathological RGC cell loss in the adult animal.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory previously reported that PD-1 is constitutively expressed in retina ganglion cells (RGCs), an unanticipated observation since PD-1 was previously believed to function exclusively within immune system (Chen et al, 2009a). Concordant with its functions in the immune system, we further demonstrated that PD-1 and its partner(s) play an important role in RGC death during retinal development (Chen et al, 2009b; Sham et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It can also be expressed on non-lymphoid organs such as retina (Chen et al, 2009). PD-L1 has a wider range of expression including dendritic cells (Wolfle et al, 2011), macrophages (Wagner et al, 2010), neutrophils (Bankey et al, 2010) and activated T and B-lymphocytes (Francisco et al, 2010;Rosignoli et al, 2009).…”
Section: Expression Of Pd-1 and Its Ligandsmentioning
confidence: 99%